Ensino de conceitos de Termodinâmica : estação meteorológica como possibilidade de aprendizagem em Física - Contin, Rita de Cássia (2017)
Among the feasible alternatives of mobilization of the educational practice in Elementary Education Science, there are several alternatives, of which we can mention the Potentially Significant Teaching Unit (UEPS) which has gained prominence, according to the results obtained, in a national scenario. Given the above mentioned, it is our aim to verify what are the possible contributions of the use of Potentially Significant Teaching Units – UEPS for the development of Physics teaching in Elementary Education; explore and investigate on how using a weather bureau contributes to Significant Learning of Elementary School students; follow, mark and consort the teaching procedures that favor meaningful learning for students; describe and analyze the experiments used in classroom practice with Elementary Education 9th graders and to deepen the concepts that involve Physics. The methodology used for data collection is qualitative in the bias of action - research, based on Trip (2005). Following this point of perspective, we used an important instrument which is a weather bureau for the application of theoretical concepts and practical experiments practiced in the process of teaching and learning, methodological strategy that enabled students to have a meaningful learning. As a result, it was verified the learning of the Elementary School 9th graders through the assay on Thermal Physics.